Childhood T-cell acute lymphoblastic leukemia in a single Latin American center: impact of improved treatment scheme and support therapy on survival - Jaime Pérez, José Carlos; Hernández de los Santos, José Antonio; Gómez Almaguer, David (2019)
Background and objective: T-cell acute lymphoblastic leukemia (T-ALL) in children representsa high-risk disease. There is a lack of studies assessing the outcome of T-ALL in Hispanicpopulations, in which it is a rare malignancy. We report the characteristics and results oftreatment for childhood T-cell ALL in children over 14 years at a Latin American referencecenter.Material and methods: From January 2005 to December 2018, there occurred the analysisof twenty patients ≤ 16 years of age from a low-income open population diagnosed ata university hospital in Northeast Mexico. Clinical and laboratory characteristics, treat-ment regimens and outcomes were assessed by scrutinizing clinical records and electronicdatabases. Diagnosis was confirmed by flow cytometry, including positivity for CD-2, 5, 7and surface/cytoplasmic CD3. Survival rates were assessed by the Kaplan-Meier method.Results: There was a male preponderance (70 %), with a 2.3 male-to-female ratio (p = .074), themedian age being 9.5 years. Leucocytes at diagnosis were ≥ 50 × 109/L in 13 (65 %) children,with CNS infiltration in 6 (30 %) and organomegaly in 10 (50 %). The five-year overall survival(OS) was 44.3 % (95 % CI 41.96–46.62), significantly lower in girls, at 20.8 % (95 % CI 17.32–24.51)vs. 53.1 % (95 % CI 50.30–55.82), (p = .035) in boys; there was no sex difference in the event-freesurvival (EFS) (p = .215). The survival was significantly higher after 2010 (p = .034).Conclusion: The T-cell ALL was more frequent in boys, had a higher mortality in girls and thesurvival has increased over the last decade with improved chemotherapy and supportivecare.